Polycard: Moulded part from natural fibre by carding technique - Luqman, Musa, Dr.; Mohd Nazry, Salleh; Suhardy, Daud; Ahmad Azrem, Azmi; Muhammad Salehin, Zakaria (Universiti Teknologi MARA, Kedah, 2010)
Invention, Innovation & Design (IID Kedah 2010), 28th - 29th July 2010 organized by Universiti Teknologi MARA (UiTM), Kedah at SP Inn, Kedah.